P31 SURGICAL MANAGEMENT OF ACQUIRED TRACHEOESOPHAGEAL FISTULA CAUSED BY ESOPHAGEAL DIVERTICULUM. (23rd November 2019) - Yifeng, Sun; Shuguang, Hao; Xufeng, Guo; Yu, Yang; Bo, Ye; Xiaobin, Zhang; Haoyao, Jiang; Zhigang, Li
Abstract: Aim: To assess the safety and feasibility of surgical treatment for acquired tracheoesophageal fistula caused by esophageal diverticulum. Background & Methods: There are rare studies of the treatment for acquired tracheoesophageal fistulas (TEFs) or bronchoesophageal fistulas (BEFs) caused by traction esophageal diverticula. Between Jan. 2014 and Apr. 2019, twelve patients were admitted to our department for TEF/BEF combined with esophageal diverticula. Clinical characteristics of the twelve patients were retrospectively reviewed. Results: Among the 12 orifices in the airway side, there were two at the carina, three at the right main bronchus and seven at the right intermediate bronchus. All orifices in the esophagus side opened at the diverticula wall. All TEF/BEFs received surgical treatment. Firstly, the fistula tunnels were dissected easily. Then, interrupted sutures repaired the fistula orifices in the airway membrane. A limited diverticulectomy with the fistula resection was done in the esophagus. Separate layers of repair were performed for the defect in the esophagus. The serratus anterior muscle flap interposition was performed in all 12 cases. There were no postoperative morbidity and mortality. No recurrence fistula and symptomatic diverticula occurred. The airway and esophagus were unobstructed during the follow-up period. Conclusion: Acquired TEF/BEFs caused by esophageal diverticula can be treated successfully by surgery. A limitated diverticulectomy is sufficient to ensure esophagus remodeling.